Muslim Heraldry and Vexillology: Origins, Developments and Controversies - Ataullah Bogda, Nordalela binti Baharudin (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Muslim Heraldry and Vexillology: Origins, Developments and Controversies